PERILAKU BERMEDIA SOSIAL PEMELUK KONGHUCU TERHADAP INFORMASI KEAGAMAAN MELALUI MEDIA SOSIAL - rini purwanti (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2018)
The Study begins from the widespread of hate through social media, hence it becomes an additional task for preachers and boards of religious organisations to make social media as medium to widespread religious messages in order to enhance religious understanding of the congregations. In this regard, the social media activists need to be aware of characters of profiles of their congregations, so that they are able to provide religious messages in informative and interesting packages. The researcher applied the AISAS model proposed by Dentsu in order to describe the attitudes of social media users among the Confucians in accessing any religious information from social media (IKMS). The AISAS was developed to observe attitudes based on the understanding that the internet becomes great, and that the users of social media currently has access to a space where they receive and send any information. In this AISAS (Attention, Interest, Search, Action, and Share) model, the key process is Attention by which the user initially receives messages, followed by Interest. Further, the user does Searches of any information, then performs Actions, and eventually Shares the information to other users. The AISAS model is not linear so that it is able to describe the attitudes of social media users. Through the AISAS model, the readers are expected to have descriptions of social-media-ing attitudes among Confucian society towards any religious information through social media.